AUTOINDUCTION PROPERTIES OF RIFAMPICIN ON JAVANESE TUBERCULOSIS WITH VARIANT TYPE CYP3A4*1G - Sutrisna, Em (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Rifampicin is one of the first-line anti-tuberculosis drugs. Rifampicin is metabolized by cytochrome P450 (CYP) 3A4. Polymorphisms of the CYP3A4 gene will affect gene expression. This leads to impaired of formation of the enzyme. The purpose of this review is to explore the effect of self-induction of Rifampicin. The results of this review showed that Rifampicin was metabolized by the CYP3A4 enzyme. Rifampicin has self-induction properties since Rifampicin also induces CYP3A4 enzyme. Rifampicin treatment repeated for 14 days leads to a shortening elimination half-life. Self-induction of CYP3A4 by Rifampicin maximum is reached after 21 days of use. Bioavailability of Rifampicin decreased from 93% to 68% after 3 weeks of treatment single dose orally. After 7 days administration of Rifampicin will increase clearance but decrease the area under the curve and Cmin. The effect of autoinduction of Rifampicin is estimated occurs after the first 6 days of administration. In individual with the variant type of CYP3A4 namely CYP3A4*1G/*1G, the effect of self-induction of Rifampicin is minimal. Keywords: Autoinduction, Rifampicin, Cytochrome P450 3A4*1G.